1993
DOI: 10.3168/jds.s0022-0302(93)77420-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Molecular Modeling of Bovine Caseins: An Energy-Minimized β-Casein Structure

Abstract: To obtain a molecular basis for the similarities and dissimilarities in the functional, chemical, and biochemical properties between beta-casein and the other caseins, a predicted three-dimensional model is presented. The predicted structure was assembled using molecular modeling techniques, as well as secondary structural prediction algorithms, in conjunction with global secondary structural information from Raman spectroscopy. To add validity to this model, the structure was refined using energy minimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(109 citation statements)
references
References 32 publications
8
97
0
4
Order By: Relevance
“…4B), the 3D model shown is (29) found that ␤-casein was more unstructured than the ␣ s -caseins, as shown on Fig. 4C, rendering this molecule more accessible to cleavage and subsequently more hydrolyzed than the other caseins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B), the 3D model shown is (29) found that ␤-casein was more unstructured than the ␣ s -caseins, as shown on Fig. 4C, rendering this molecule more accessible to cleavage and subsequently more hydrolyzed than the other caseins.…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation of hydrolyzed regions by casein 3D modeling. 3D molecular-modeling representations of the caseins, deduced from the data of Kumosinski et al (28) for ␣ s1 -casein, Farrell et al (9) for ␣ s2 -casein, and Kumosinski et al (29) for ␤-casein, are shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…Leu 192 -Tyr 193 is the easiest hydrolyzed bond, also the most susceptible to attack by chymosin and other milk-clotting enzymes (Pélissier et al, 1974;Creamer, 1976;Visser and Slangen, 1977;Carles and Ribadeau-Dumas, 1984). Indeed, in the molecular model of -CN predicted by Kumosinski et al (1993), this region is exposed on the (monomer) surface and accessible to enzyme action. Chymosin cleaves two peptide bonds in the sequence Ala 189 -Phe-Leu-Leu-Tyr 193 of -CN, whereas cardosin cleaves all four bonds under the same conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In figure 7 we present three-dimensional models for both caseins in solution based on the structures predicted by Kumosinski et al [1991Kumosinski et al [ , 1993 ( fig. 7 a and d for κ-and β-casein, respectively).…”
Section: Discussionmentioning
confidence: 99%